Mesopotamian Sculpture from the Protoliterate Period to the Agade Dynasty - Wootton, Julian Eric
M.A.; Einteilung der Arbeit: I. The Protoliterate Period: Sculpture from Warka, Ur, Khafajeh, Tel Brak; II. The Early Dynastic Period: Tel Asmar, Khafajeh, Tel Agrab, Mari, Assur, Nippur, Umma, Adab, Warka, Ur, al-Ubaid, Lagash; III. The Period of the Dynasty of Agade (The Akkadian Period): Reliefs and sculptures in the round.